Adjuvant non-bacteriolytic and anti-inflammatory combination therapy in pneumococcal meningitis: an investigation in a mouse model. (January 2019) - Klein, M.; Höhne, C.; Angele, B.; Högen, T.; Pfister, H.W.; Tüfekci, H.; Koedel, U.
Abstract: Objectives: Therapy with antibiotics, dexamethasone, and supportive intensive care has improved the prognosis of pneumococcal meningitis, but mortality remains high. Here, we investigated an adjunctive combination therapy of the non-bacteriolytic antibiotic daptomycin plus several anti-inflammatory agents to identify the currently most promising adjunctive combination therapy for pneumococcal meningitis. Methods: C57BL/6 mice were infected by injection of pneumococci into the cisterna magna. Treatment was begun 21 h after infection, and consisted of ceftriaxone plus (a) dexamethasone, (b) dexamethasone plus daptomycin, (c) daptomycin, (d) daptomycin plus an anti-IL1 antibody, (e) daptomycin plus roscovitine, or (f) daptomycin plus an anti-C5 antibody. Animals were followed until 45 h after infection. Furthermore, adjunctive daptomycin plus anti-C5 antibodies were assessed in a long-term follow-up. Results: Adjunctive treatment with daptomycin and an anti-C5 antibody was superior to adjunctive dexamethasone and reduced disease symptoms (clinical score 1.1 ± 1.1 versus 5.0 ± 2.7, p < 0.0083), improved explorative activity (open field test 17.8 ± 8.2 versus 7.4 ± 4.3 crossed fields/2 minutes, p < 0.0083), and reduced hearing impairment (thresholds for click stimulus 96.1 ± 14.7 versus 114.8 ± 9.3 dB SPL, p < 0.0083) in the acute stage. Furthermore, explorative activity (14.4 ± 7.3 crossed fields/2 minutes versus 6.3 ± 7.2, p < 0.05) and cognitive function (t-maze test, exploration time previously unknown alley 72.4 ± 14.3 versus 48.7 ± 25.6%, p < 0.05) was improved at 2 weeks after infection. Treatment with daptomycin plus an anti-IL-1β antibody or roscovitine was not of significant benefit in comparison to adjunctive therapy with dexamethasone. Conclusions: An adjunctive combination of the non-lytic antibiotic daptomycin plus an anti-C5 antibody was superior to standard therapy with adjunctive dexamethasone in the treatment of pneumococcal meningitis.